(untitled) (Zaporizhzhia Historical Review, 2021)
In the article ´Hustav Adolph and Ungshturm Adolph Hitlerís activity (1922ñ1925)ª peculiarity of the origin process of the national-socialism of the youth organization on the territory of Weimar republic is revealed. The author analyses of the history of the youth policy of NSDAP in 1922ñ1925s, which is not absolutely known.